Alcohol consumption, dating relationships, and preliminary sexual outcomes in collegiate natural drinking groups. Issue 12 (29th October 2013) - Devos‐Comby, Loraine; Daniel, Jason; Lange, James E.
Abstract This study tested the effects of committed relationships and presence of dates on alcohol consumption and preliminary sexual outcomes in natural drinking groups (NDGs). Undergraduate drinkers (N = 302) answered an online questionnaire on their most recent participation in a NDG. The interaction between relationship commitment and presence of a date on alcohol consumption was significant. Among students not in committed relationships, those dating within their NDG reported heavier drinking than those not dating. Students in committed relationships drank less than those who were not committed only when their partners were present. The positive correlation between drinking and sexual contact was significant only for those who were not in committed relationships. Implications for future research and interventions are discussed.